Mixed infections with tick-borne viruses in a seabird colony in Eire - Nuttall, P A; Kelly, T C; Carey, D; Moss, S R; Harrap, K A (Archives of virology, 1984)
Viruses were isolated from 2 tick species collected from the nesting areas of seabirds on Great Saltee Island, Eire. Bunyaviruses of the Uukuniemi serogroup were isolated from hard ticks (Ixodes uriae and I. rothschildi), bunyaviruses of the Hughes serogroup from soft ticks (Ornithodoros maritimus), and orbiviruses of the Kemerovo serogroup from I. uriae and O. maritimus. The results indicate that the bunyaviruses, but not the orbiviruses, show "tick specificity". Neutralising activity against members of all 3 serogroups was detected in sera from chicks in the nesting areas; neutralising antibodies were probably maternal.